The role of concurrent engineering in cost optimization - Obuamamh, Ali husam Mohameed; Al-Hamdani, Bahaa Hussein (Journal of Economics and Administrative Sciences, 2021)
The research aims to study and analysis of concurrent engineering (CE) and cost optimization (CO), and the use of concurrent engineering inputs to outputs to improve the cost, and the statement of the role of concurrent engineering in improving the quality of the product, and achieve savings in the design and manufacturing time and assembly and reduce costs, as well as employing some models to determine how much the savings in time, including the model (Lexmark) model (Pert) to determine the savings in design time for manufacturing and assembly time. To achieve the search objectives, the General Company for Electrical and Electronic Industries Refrigerated Engine Laboratory is selected and specifically engine 1/4 horse located in Baghdad, as synchronized engineering technology has been implemented in the company, which is appointed as the company to improve its costs through improved costs Quality and low time and cost less. The researcher reached a set of conclusions and recommendations and conclusions highlighted the following: The technique of simultaneous engineering of the most appropriate technologies for the business environment and accompanied by rapid changes and their importance to the research sample, The work according to concurrent engineering (proposed situation) makes it on the basis of collective cooperation and simultaneous, and products are developed faster through the simultaneous performance of the operations of product development, especially product and process design. Either the most important recommendations of the following: economic units should interest techniques Alklfoah and management of Nha concurrent engineering technology because it is an important tool to improve and develop existing and new products. Economic units of attention as a source of power customer economic unity, by involving customers in the design process and product development in the form that suits their desires, and conduct field studies and research in the market to learn about their needs and desires. The need for attention to design cost (DTC) in order to make products close to customers, ie by making the design viable products to buy and take into account the design team equally acceptable quality